Mid-Cenozoic ostracod biostratigraphic range extensions and taxonomic notes on selected species from a new Oligocene (Duntroonian–Waitakian) fauna from southern New Zealand. Issue 4 (2nd October 2017) - Ayress, Michael; Robinson, Jeffrey; Lee, Daphne
Abstract : AYRESS, M., ROBINSON, J.H. & LEE, D.E., March 2017. Mid-Cenozoic ostracod biostratigraphic range extensions and taxonomic notes on selected species from a new Oligocene (Duntroonian–Waitakian) fauna from southern New Zealand. Alcheringa 41, 487–498. This paper discusses a highly diverse assemblage of Ostracoda, particularly biostratigraphically useful species, from a richly fossiliferous shallow-marine deposit of late Oligocene age on Cosy Dell farm, near Waimumu, Southland, New Zealand. The ostracod fauna, consisting of 126 species, is yet to be fully analysed, although it is clear that this new window into the nearshore fauna of the mid-Cenozoic provides the earliest records of many characteristic extant New Zealand genera and species, including several species hitherto only known as far back as the early Miocene (Otaian–Altonian New Zealand local Stages). Finding these younger species in an Oligocene deposit was unexpected and indicates that our current knowledge of mid-Cenozoic ostracod age ranges, particularly for nearshore species, is incomplete. Using nannofossils and molluscs, the Cosy Dell deposit is dated as late Oligocene (Duntroonian or lower Waitakian local Stages) in age; therefore, the new ostracod species occurrences described here are considered valid range extensions. Although the biostratigraphic application of the benthonic ostracod species discussed is limited owing to the effects of sedimentary facies and other palaeoenvironmental factors, the ostracod fossil record does include significant extinction and inception events that offer correlative potential for mid-Cenozoic stratigraphical studies. This study identified a need for modern illustration of many species, and we provide scanning electron microscope illustrations of those Cosy Dell taxa previously considered biostratigraphically useful, as support for species identification and associated biostratigraphic conclusions. Michael Ayress [mike.ayress@rpsgroup.com ], RPS ichron Group, Gadbrook Business Centre, Northwich CW9 7TN, UK; Jeffrey Robinson [jeffreyhrobinson@yahoo.co.nz ] and Daphne Lee [daphne.lee@otago.ac.nz ], Geology Department, University of Otago, Dunedin, New Zealand